Physical and Numerical Modelling of Rockwool Insulated Landfill Liner Materials as a Heat Mitigation Method - Widjaja, Emmanuella Stephanie; Ahmad, Afnan; Kumar, Manoj; Anggraini, Vivi (Himpunan Ahli Teknik Tanah Indonesia, 2024)
The growing global amount of waste emphasizes the urgency of effective landfill management. The large amount of organic matter in landfill liners undergoes rapid biodegradation, generating significant heat. This heat production can cause various environmental issues, such as the release of volatile organic compounds, an increased risk of groundwater contamination from leachate migration, unpleasant odors, and a reduction in the structural integrity of the landfill liner. Therefore, efficient heat mitigation methods in landfill liners are crucial for minimizing detrimental environmental effects. Utilizing insulation material in landfills can be an effective and novel method in the environmental geotechnical field while promoting material sustainability. This study aims to evaluate the effectiveness of rockwool as an insulation material in reducing heat transfer inside landfill liners. The effectiveness of rockwool was assessed by using both physical and numerical modelling with varying thicknesses of rockwool, moisture conditions, and elevated temperatures in the landfill liner system. The insulated landfill liner system was simulated numerically using ANSYS software. A wooden box prototype was built to simulate a real-life insulated landfill liner system to evaluate the feasibility of insulation material as a heat mitigation method in landfills. The findings suggest that rockwool is effective in mitigating the heat in landfill liners. Overall, rockwool reduced the elevated temperatures up to 48.45% despite the system being wet which reduces the effectiveness of insulation performance. Comparatively, the 20 mm rockwool was efficient in minimizing average level of elevated temperatures, meanwhile, rockwool with thicknesses of 35 mm and 50 mm were needed to attenuate extremely elevated temperatures. These results were demonstrated through numerical simulation and validated by physical modelling results. It can imply an effective method for mitigating heat in landfill liners, which advances the development of environmental geotechnics for sustainable waste management.